The development of the eastern Orpheus rift basin, offshore eastern Canada: A case study of the interplay between rift-related faulting and salt deposition and flow. (May 2022) - Hanafi, Bari R.; Withjack, Martha O.; Durcanin, Michael A.; Schlische, Roy W.
Abstract: The salt-rich Orpheus rift basin, part of the eastern North American (ENAM) rift system, formed during the Late Triassic to Early Jurassic prior to opening of the Atlantic Ocean. Using a dense grid of 2D seismic-reflection lines, data from nearby wells, and information from adjacent ENAM rift basins, we have established a tectonostratigraphic framework, identified key structural elements, and reconstructed the deformation history for the eastern part of the basin. Our work shows that a series of E-striking, S-dipping faults with normal separation bound the basin on the north. Deformation within the basin is complex with forced folds above deep-seated intrabasin faults, detachment folds, detached thrust faults, and salt diapirs. The synrift evaporite sequence consists of an older massive salt unit that underlies a younger unit with two distinct interfingering facies. Facies A, consisting of salt and interbedded sedimentary rocks (likely shales), developed near the border-fault system and its relay ramps. Facies B, consisting of massive salt with few interbedded sedimentary rocks, developed toward the basin center. The youngest synrift unit accumulated exclusively within minibasins near the northern border-fault system. Based on location, this youngest synrift unit likely consists of coarse-grained and poorly sorted alluvial-fan or talus-slope deposits shed from the footwall. All synrift units are intruded by igneous sheets likely associated with the Central Atlantic Magmatic Province and, thus, are mostly Late Triassic in age (or possibly older). The border-fault system profoundly affected deposition within the eastern Orpheus rift basin by providing pathways for clastic sediment input into the salt-rich basin. These depositional patterns subsequently influenced deformation associated with lateral salt flow during minibasin formation. In regions with interbedded salt, detachment folds and thrust faults developed, whereas salt walls and stocks developed in regions with more massive salt. Highlights: The Orpheus rift basin, part of the eastern North American rift system, developed during the Late Triassic to Early Jurassic. The salt-rich rift basin exhibits a complex array of basement-involved and detached structures. Rift-related faulting and mechanical stratigraphy of the synrift salt influenced the style of deformation within the basin. Detached shortening-related structures developed during minibasin formation during and shortly after rifting.